Cannabinoid facilitation of fear extinction memory recall in humans - Rabinak, Christine A.; Angstadt, Mike; Sripada, Chandra S.; Abelson, James L.; Liberzon, Israel; Milad, Mohammed R.; Phan, K. Luan (Neuropharmacology, 2013)
A first-line approach to treat anxiety disorders is exposure-based therapy, which relies on extinction processes such as repeatedly exposing the patient to stimuli (conditioned stimuli; CS) associated with the traumatic, fear-related memory. However, a significant number of patients fail to maintain their gains, partly attributed to the fact that this inhibitory learning and its maintenance is temporary and conditioned fear responses can return. Animal studies have shown that activation of the cannabinoid system during extinction learning enhances fear extinction and its retention. Specifically, CB1 receptor agonists, such as Δ9-tetrahydrocannibinol (THC), can facilitate extinction recall by preventing recovery of extinguished fear in rats. However, this phenomenon has not been investigated in humans. We conducted a study using a randomized, double-blind, placebo-controlled, between-subjects design, coupling a standard Pavlovian fear extinction paradigm and simultaneous skin conductance response (SCR) recording with an acute pharmacological challenge with oral dronabinol (synthetic THC) or placebo (PBO) 2 h prior to extinction learning in 29 healthy adult volunteers (THC = 14; PBO = 15) and tested extinction retention 24 h after extinction learning. Compared to subjects that received PBO, subjects that received THC showed low SCR to a previously extinguished CS when extinction memory recall was tested 24 h after extinction learning, suggesting that THC prevented the recovery of fear. These results provide the first evidence that pharmacological enhancement of extinction learning is feasible in humans using cannabinoid system modulators, which may thus warrant further development and clinical testing. This article is part of a Special Issue entitled ‘Cognitive Enhancers’. ► Δ9-tetrahydrocannabinol (THC) facilitates extinction of conditioned fear in humans. ► THC attenuated spontaneous recovery of fear (vs. placebo). ► THC did not affect within-session extinction learning. ► Cannabinoids may facilitate exposure-based therapy in patients with anxiety.